Perancangan Aplikasi Pengenalan Pariwisata Kabupaten Kuantan Singingi Berbasis Android Menggunakan Layanan Location Based Service (LBS) - Ramadhan Ramadhan; Feri Candra (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Kuantan Singingi is one of the regencies in Riau Province which is visited by many tourists every year, this is because in Kuantan Singingi there is a ‘Pacu Jalur’ event that is held every year and this event is included in the National tourism calendar. With the inclusion of ‘Pacu Jalur’ in the National Calendar of Events causing many tourists both in the city, out of town and international tourists who come to visit Kuantan Singingi, therefore the purpose of this research is to develop tourism applications that can facilitate tourists to access tourist information in Kuantan Singingi This application uses the LBS service and can be used via android. The stages of designing this tourism application using the Waterfall method. Waterfall is a systematic and sequential development model that links one phase to another in sequence. This research resulted in an Android-based Kuantan Singingi Tourism App that can be used by tourists to find information about tourism in Kuantan Singingi. Keywords: Location Based Service, Android, Waterfall Method, Tourism, Kuantan Singingi